Coverage and content analysis of biotechnology and genetically modified organisms in four selected Nigerian daily newspapers (2013)
The media, especially the newspapers play a major role as sources of biotechnology information and will be useful avenues for disseminating related information. It is in view of this that this study examined coverage of biotechnology and Genetically Modified Organisms (GMOs) in Nigerian daily newspapers as an avenue to raise mass awareness especially amongst literate farmers. This study content analysed 63 GMOs and biotechnology items framed in four Nigerian newspapers (the Guardian, Punch, Vanguard and Nigerian Tribune). The time frame was from January 1, 2005 to December 31, 2010 being the period that marked the sudden rise in public awareness of biotechnology issues occasioned by coverage of biotechnology related news in Nigerian media. Variables measured include types of news, frequency of news coverage, placement, direction and space allotted to biotechnology news and related stories. Data were analysed using both descriptive (frequencies, percentages) and inferential (ANOVA) statistics at p≤0.05. Results indicate that across the four newspapers, types of biotechnology news reported were mostly food safety news (54.0%) in 2005 (21 items) with highest news items from Tribune (49.0%). Though most news items (87.3%) on GMOs and biotechnology were positively framed, all (100%) news items were not strategically placed as they were in other pages of all the newspapers. Space allocated to biotechnology news was higher in the Punch (469cm2) than Guardian (423 cm2), Tribune (378 cm2) and Vanguard (252 cm2). There were significant difference across the newspapers in direction (F= 1.23, p ≤ 0.05) and space allotted (F = 2.53, p ≤ 0.05) to coverage of biotechnological news. Generally, there is low reportage of biotechnology and GMOs news for the period investigated, across newspapers, in space allotment and strategic locations; it is therefore recommended that more attention and priority should be accorded biotechnology news items in terms of space and strategic placement to enhance public awareness of related information.